2015
DOI: 10.3109/14767058.2014.974537
|View full text |Cite
|
Sign up to set email alerts
|

Differential oxidative stress levels in mothers with preeclampsia delivering male and female babies

Abstract: The altered levels of oxidative stress and antioxidant enzymes in mothers with PE delivering male babies suggest that they may be at higher risk for developing metabolic and neurodevelopmental disorders than female babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Inflammation, oxidative stress, and angiogenic imbalance have been suggested to contribute to PE pathogenesis (Chaiworapongsa, Chaemsaithong, Yeo, & Romero, ; Roy et al, ). PE patients usually have increased proinflammatory factors stimulating the production of anti‐angiogenic protein, soluble FMS‐like tyrosine kinase‐1 (sFlt‐1) (Freeman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, oxidative stress, and angiogenic imbalance have been suggested to contribute to PE pathogenesis (Chaiworapongsa, Chaemsaithong, Yeo, & Romero, ; Roy et al, ). PE patients usually have increased proinflammatory factors stimulating the production of anti‐angiogenic protein, soluble FMS‐like tyrosine kinase‐1 (sFlt‐1) (Freeman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased peripheral inflammation and O & NS have been demonstrated to be associated with various obstetric complications, including preeclampsia (Kirbas et al, 2016;Ma et al, 2015;Nossier et al, 2015), glucose intolerance (Zein et al, 2016), miscarriage, fetal anomaly and growth restriction and preterm labor (Duhig et al, 2016;Mukhopadhyay et al, 2015). Moreover, these pathways may also affect neonate's outcomes, including lowered Apgar scores (Rejc et al, 2016), increased risk of asthma (Noutsios and Floros, 2014), poorer neurodevelopment outcome (especially among male babies) (Roy et al, 2015), and other specific diseases of the neonatal period, such as bronchopulmonary dysplasia, retinopathy of prematurity, necrotizing enterocolitis, and periventricular leukomalacia (Marseglia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is crucial in the vasculogenesis and angiogenesis involved in placental development . Inflammation, oxidative stress and angiogenic imbalance have also been suggested to contribute to PE . The association of both inflammatory processes and oxidative stress, and their possible role in cellular pathology was reviewed elsewhere .…”
Section: Introductionmentioning
confidence: 99%
“…10 Inflammation, oxidative stress and angiogenic imbalance have also been suggested to contribute to PE. 11 The association of both inflammatory processes and oxidative stress, and their possible role in cellular pathology was reviewed elsewhere. 12 It was also reported that imbalance between anti-and pro-inflammatory cytokines is a potential cause of PE.…”
Section: Introductionmentioning
confidence: 99%